ANALISIS PBOLEMATIKA PESERTA DIDIK DALAM MENGATASI KESULITAN BELAJAR DITINJAU DARI FAKTOR EKSTERNAL (METODE MENGAJAR GURU) DI SDN BANARAN 4 SRAGEN - Miratu Chaeroh; Sheren Dwi Oktaria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning problems can be understood as a variety of obstacles, challenges, or constraints that arise during the course of the teaching and learning process and have the potential to reduce the success of achieving educational goals. This study was conducted to examine the various problems experienced by students in the face of learning difficulties that come from external factors, especially related to the teaching methods of teachers at SDN Banaran 4 Sragen. Learning difficulties are one of the disorders that often occur in learning activities and can affect the learning outcomes of learners. This study uses a qualitative descriptive approach with data collection techniques in the form of observation and interviews. Research subjects include students and classroom teachers at SDN Banaran 4 Sragen. The results of observations and interviews on several aspects showed an average percentage of 50% with sufficient categories, which means that the learning methods used by teachers are not fully in the very good category. The findings of the study also revealed that one of the external factors that trigger learning difficulties is the less varied and less developed teaching methods of teachers.